Batik web-based courseware: the integration of assure model in developing the courseware as an effective teaching medium in visual arts education subject / Norraidah Mohamad Omar - Omar, Norraidah Mohamad (2014)
This study presented Batik Web-Based Courseware (BWBC) as an effective instructional based teaching material. This web-based courseware was developed focusing on the historical of Batik craft to help visual art teacher in daily teaching. Batik web-based courseware (BWBC) is the platform for Visual Art Education (VAE) teachers to teach, share and explore knowledge, during their teaching session.. The research question rises based on a possibility of BWBC that employs a non-linear, problem-based, teachers-centred, constructivist approach to assist teachers in their teaching. The uniqueness of this BWBC is combined various types of Batik craft in one complete teaching courseware. This study is discursive the effectiveness of BWBC developed by referring to the ASSURE Model design in developing as an effectiveteaching medium. Keywords : Batik Web-Based Courseware (BWBC), Assure Model, Effective Teaching Medium, Visual Art Education